2017
DOI: 10.1186/s12970-017-0180-0
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic diet benefits body composition and well-being but not performance in a pilot case study of New Zealand endurance athletes

Abstract: BackgroundLow-carbohydrate, high-fat and ketogenic diets are increasingly adopted by athletes for body composition and sports performance enhancements. However, as yet, there is no consensus on their efficacy in improving performance. There is also no comprehensive literature on athletes’ experiences while undertaking this diet. The purpose of this pilot work was two-fold: i. to examine the effects of a non-calorie controlled ketogenic diet on body composition and performance outcomes of endurance athletes, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 29 publications
5
84
1
2
Order By: Relevance
“…This is in accordance with published data from healthy subjects and athletes, which also performed well under LCD and KD regimes [18][19][20][21]. While some studies showed a negative impact when switching to LCDs or KDs on physical performance in the short term (21-30 days; [22]) and up to 10 weeks [23], the duration of 20 weeks in our study allowed the patients to adapt to the profound change in energy metabolism. Accordingly, at T20, none of the KD and LCD patients reported "lack of energy", and their physical performance was even superior to patients in the SD group.…”
Section: Limitations and Strengths Of The Studysupporting
confidence: 92%
“…This is in accordance with published data from healthy subjects and athletes, which also performed well under LCD and KD regimes [18][19][20][21]. While some studies showed a negative impact when switching to LCDs or KDs on physical performance in the short term (21-30 days; [22]) and up to 10 weeks [23], the duration of 20 weeks in our study allowed the patients to adapt to the profound change in energy metabolism. Accordingly, at T20, none of the KD and LCD patients reported "lack of energy", and their physical performance was even superior to patients in the SD group.…”
Section: Limitations and Strengths Of The Studysupporting
confidence: 92%
“…Therefore, it should be assumed that the daily energy expenditure of all studied subgroups was at a similar level. Hence, it should be concluded that the significantly lower BMI and fat content in subgroup C than in subgroups WL and TT demonstrated by the post hoc test are the expression of a different lifestyle of these women, including the wrong diet, which modified their body composition and weight [36]. The small amounts of energy ingredients supplied to the body in all subgroups, i.e.…”
Section: Discussionmentioning
confidence: 85%
“…In an animal model, however, eight weeks of KD significantly enhanced the endurance capacity of C57/BL6 mice (Zinn et al, 2017); a correlation existed between body weight and running time until exhaustion with mice on heavier a KD running longer. This was attributed to keto-adaptation (Zinn et al, 2017). Since there was an inter-individual difference, the subjects possessing higher metabolic flexibility may prefer KD and reflect the weight change.…”
Section: Ketogenic Diet and Endurance Exercisementioning
confidence: 86%
“…These results explain the partial mechanisms by which keto-adaption showed great potential in improving endurance exercise capacity. However, other researchers have reported that KD increased benefit in body composition and wellbeing but failed to enhance endurance capacity (Zinn, Wood, Williden, Chatterton, & Maunder, 2017).…”
Section: Ketogenic Diet and Endurance Exercisementioning
confidence: 96%
See 1 more Smart Citation